Content Validity of a Measurement Instrument for the Reception of the “Virtual” Mass - Hidalgo-Díaz, Pedro (2024)
The health emergency condition produced by COVID-19 generated, as a preventive measure, quarantine in various parts of the world, making it impossible for the Catholic Church to celebrate. One response toward this situation was the transmission of the mass by digital means. In this study, an instrument to measure the reception that the transmission of the “virtual” mass has achieved among the Catholics and the assessment of the said experience was developed. Its design is instrumental because content validity has been carried out through expert judgment. Aiken’s V coefficient indicates that the degree of agreement between them was greater than 70, concluding that the instrument is good and therefore valid.